Education for sustainable development in Polish institutions of higher education – present and future - Lorek, Agnieszka; Lorek, Elżbieta; Koczur, Wiesław (Economics and Environment, 2023)
Education for sustainable development is still developing as a broad and comprehensive concept that includes related content on the environment, economy and society. Key issues of sustainable development include, among others, economic issues, production and consumption models, natural resource management, environmental protection, development models, poverty reduction, civic rights, democracy, governance etc. These issues are very diverse and require a holistic approach to teaching. The objective of this article is to diagnose and evaluate the current state of education for sustainable development in Polish higher education institutions, with particular emphasis on the EU in Katowice and to identify the directions of change. This article was written based on the Authors’ many years of scientific and teaching experience. It was also supported by a survey conducted in the year 2020/2021 among the students at the University of Economics in Katowice, which allowed them to identify directions for future educational activities.